TO THE ISSUE OF FIRMNESS OF SLAG FOAMS IN STEELMAKING POOL - N. V. Andrianov; A. A. Chichko (Литьë и металлургия, 2005)
The main questions of formation and firmness of cindery foam in conditions close to the realized in blast-steel-making-furnace are considered. The nature of factors, stabilizing and breaking the cindery foam, is analyzed.